Flexural Behaviour of Non-Autoclaved Pre-Stressed High-Strength Concrete Pipe Piles with Different Rubber Contents - Jiahao Wen; Feng Liu; Fei Yang; Dawei Chen; Jia Liu; Gang Xu; Haofan Chen; Xu Liang; Guangcheng Ding; Xiaohui Li (Buildings)
Non-autoclaved pre-stressed high-strength rubber-modified concrete (NA-PHRC) pipe piles were developed to address the high energy consumption and brittleness of existing pre-stressed high-strength concrete (PHC) pipe piles. The comparative flexural test results showed that the deformation capacity of NA-PHRC pipe piles improved, which was correlated with the rubber content. However, both the cracking moment and the ultimate moment decreased. When the rubber content is 5% and 10%, the cracking moment decreases by 3.85% and 7.69%, respectively, while the ultimate moment decreases by 3.75% and 7.28%. Additionally, the theoretical calculation results of the influence of rubber on the cracking and ultimate moments were consistent with the experimental results. Thus, this innovative NA-PHRC pipe pile can be applied in environments that require high durability.